Pengaruh Likuiditas dan Profitabilitas terhadap Shareholder Returns Perusahaan Makanan dan Minuman Tercatat di Bursa Efek Indonesia - Mursalim Nohong; Nur Alamzah; Yulianti Yulianti (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The impact of liquidity and profitability on stock earnings of food and beverage companies listed on the Indonesian Stock Exchange. The purpose of this study is to examine whether the liquidity ratio (current ratio, cash ratio) and profitability (ROA, ROE) affect the return on equity of food and beverage companies listed on the Indonesian Stock Exchange. That is. The data collection techniques used were performed using documented methods. The test used in this study is multiple linear regression used as an analytical tool, and t-test and f-test are used to test hypotheses. The results of this study suggest that the liquidity ratio has a partial positive but minor impact on stock returns. Profitability (ROA has a positive impact, but is not significant, while ROE has a large positive impact on stock returns). On the other hand, the liquidity ratio (current ratio, cash ratio) and profitability ratio (ROA, ROE) will affect the stock returns of food and beverage companies listed on the Indonesian Stock Exchange for the period 2016-2020. I won't givekeyword:Equity returns, liquidity and profitability. Keywords: liquidity, profitability, shareholders, Indonesian stock exchange